Sexuality in the old testament: a review article - Souza, Elias Brasil de (Kerygma, 2007)
Flame of Yahweh is a broad and detailed research written from a conservative perspective by Richard Davidson. As the author himself states, this work “undertakes the Brobdingnagian task of examining every passage of the Hebrew Bible (HB) dealing with human sexuality, in an attempt to lay bare the basic contours of a theology of human sexuality in the final (canonical) form of the OT” (p. 2). In order to accomplish this goal, Davidson builds on previous research and provides his own original exegesis in several of the passages and topics discussed. One of the central premises of Davidson’s work is the notion that the Edenic pattern for sexuality constitutes the foundation for the rest of the OT perspective on the topic (p. 3). Consistent with this premise, he provides a comprehensive and, at the same time, detailed exposition of the Old Testament concept of sexuality. An introduction, providing a helpful survey the OT sexual vocabulary, is followed by fourteen chapters divided into three sections. An afterword, drawing some implications for a New Testament theology of sexuality, closes the book.